A influência de organizações didáticas no trabalho matemático dos estagiários da licenciatura: um estudo da função exponencial - Freitas, Rita Lobo (2015)
This study aimed to investigate the behavior of students in a Mathematics degreecourse at a state university in Bahia, in order to understand how these individuals mobilize their mathematical and didactic knowledge built during graduation and during the process of experimentation about the exponential function. We intend, in this research, answer the following question: How do didactic organizations interfere in the construction of trainee's knowledge of mathematics degree about the concept of exponential function? As methodology, we used Artigue's Didactic Engineering (1988). The theoretical Frame work used was the Theory of Didactic Situations of Brousseau (1996, 2008) and Anthropological Didactics Theory of Chevallard (1999). ln the construction of problem Situations we supported in selected activities from analyzed textbooks and historical and epistemological study of mathematical object called exponential function. The proposed activities in a didactic sequence had been adapted in order to suit the characteristics of a milieu antagonistic, including software use (Geogebra and Excel). The analysis of collected data in experimentation stage, allowed to identify a group of positive characteristics which showed the influence of didactic organization in construction and consolidation of the students' knowledge, are these mathematical or didactic knowledge about exponential function